Advancements in Endoscopic Biliary Interventions by Gastroenterology - Almuhaidb, Aymen; Olson, Dylan; Aadam, A. Aziz (Seminars in Interventional Radiology, 2021)
Endoscopic retrograde cholangiopancreatography (ERCP) is an endoscopic technique in which a specialized side-viewing endoscope is guided into the duodenum, allowing for instruments to access the biliary and pancreatic ducts. ERCP was initially developed as a diagnostic tool as computed tomography was in its infancy during that time. ERCP has evolved since its inception in the 1960s to becoming not only a valuable diagnostic resource but now an effective therapeutic intervention in the treatment of various biliary disorders. The most common biliary interventions performed by ERCP include the management of biliary obstructions for benign and malignant indications. Additionally, endoscopic ultrasound (EUS) has been increasingly utilized in diagnosing and intervening on pancreaticobiliary lesion. This article will discuss the various methods currently available for various endoscopic biliary interventions and future interventional techniques. For the management of biliary strictures, EUS can be utilized with fine need aspiration, while ERCP can be used for the placement of various stents and diagnostic modalities. Another example is radiofrequency ablation, which can be used for the treatment of hilar strictures. Achieving bile duct access can be challenging in patients with complicated clinical scenarios; other techniques that can be used for bile duct access include EUS-guided rendezvous approach, transluminal approach, Choleodochoduodenostomy, and hepatogastrostomy, along with gaining access in complicated anatomy such as in patients with Rou-en-Y anatomy. Another useful endoscopic tool is nonsurgical drainage of the gallbladder, which can be a suitable option when patients are not optimal surgical candidates. There has also been an increase in outpatient utilization of ERCP, which was previously seen as a predominantly inpatient procedure in the past. Possible future evolutions of biliary interventions include robotic manipulation of a duodenoscope and direct infusion of chemotherapeutic or immunomodulatory agents into the pancreaticobiliary tree. These advancements will depend on parallel advancements in other imaging and laboratory as well as breakthrough technology or techniques by other disciplines including interventional radiology and minimally invasive surgery.
Keywords: endoscopic biliary interventions; advanced endoscopy; gastroenterology